Effects of mid-season drainage on iron toxicity, rice yield, and water productivity in irrigated systems in the derived savannah agroecological zone of West Africa - Dossou-Yovo, Elliott Ronald; Kouadio, S.A.K.; Saito, Kazuki (Elsevier, 2023)
Context: Increasing rice yield is crucial for meeting the demand of the fast-growing population in sub-Saharan Africa. Mid-season drainage can reduce iron toxicity, which is one of the major constraints to rice production in this region, and increase rice yield and water productivity. Objectives: The objectives of this study were to evaluate the effects of mid-season drainage on iron toxicity, rice yield, and water productivity and identify the factors that favor rice yield in the fields with mid-season drainage relative to continuous flooding. Methods: Experiments were conducted during the wet season over two years in 30 farmers’ fields in two irrigated schemes in the region of Bouake, central Cˆ ote d ′Ivoire. Each farmer’s field was subdivided into three plots consisting of three water management practices: continuous flooding, mid-season drainage at 25 days after transplanting followed by two drying phases of seven days each separated by a flooded phase of three days or by alternate wetting and drying. Results: Large variations in soil properties, management practices, iron toxicity score (based on leaf bronzing), rice yield, and water productivity were observed in farmers’ fields. Under continuous flooding, lower rice yield was associated with higher iron toxicity, and this was observed in the fields with higher soil organic carbon, and in which farmers applied lower amounts of phosphorus fertilizer. Mid-season drainage practices significantly reduced iron toxicity, irrigation water amount, and relatively increased water productivity. On average across farmers’ fields, rice yield was not significantly different among water management practices. However, when data at the individual field level were considered to calculate differences between the treatments, gains in rice yield in the fields with mid-season drainage at 25 days after transplanting followed by alternate wetting and drying relative to continuous flooding were associated with higher soil organic carbon, earlier application of the second split of fertilizer, and a large reduction in the iron toxicity score in the fields with mid-season drainage at 25 days after transplanting followed by alternate wetting and drying compared to continuous flooding. Conclusions: Mid-season drainage at 25 days after transplanting followed by alternate wetting and drying combined with appropriate fertilizer management could be recommended to the smallholder farmers to reduce iron toxicity, and increase rice yield and water productivity in fields with high soil organic carbon and iron toxicity. Significance: This study addressed a gap in the literature concerning the potential of mid-season drainage to reduce iron toxicity, and increase rice yield and water productivity and the suitable domains for its application.